Augmenting Chroma Performance for WLED Employing Sr8ZnSc(PO4 )7:Eu2+@SiO2 as a Scattering-Enhancing Substance - Cong, Pham Hong; Anh, Nguyen Doan Quoc (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Featuring the B-Ca3(PO4)2 phosphor system, Sr8ZnSc(PO4)7:Eu2+ (SZSPOE) phosphor can be used as an alternative to YAG:Ce3+ yellow phosphor for the advancement of the white light-emitting diode (WLED). Its potentials are demonstrated in this paper, including the expected emission power and wavelength based on the previous studies and its impacts on WLED illumination properties employing Mie-theory-based scattering simulation and calculation and MATLAB software. SZSPOE phosphor can display a wide yellow discharge peaking at 511 and 571 nm and a redshift upon the increase in doped Eu2+ dosage. A phosphor layer comprised of SZSPOE phosphor, SiO2 particles, and silicone gel is simulated for making a WLED. The WLED performance is observed with varying SiO2 amount. Changes in simulation results of the WLED’s lighting properties can be attributed to the scattering within the phosphor layer in response to different SiO2 concentrations. Results demonstrate that increasing SiO2 amount can lead to the better spatial color distribution uniformity and luminous output of the WLED. Meanwhile, the lower color rendering index is observed owing to the insufficient red light power. However, the improvement in color uniformity and luminosity alongside the emission tunability of the SZSPO host, SZSPOE phosphor can be a promising candidate for substituting the original YAG:Ce3+ for advanced WLEDs.